FORMATION OF A HEALTHY LIFESTYLE AMONG WOMEN THROUGH THE WIDE PROMOTION OF MASS SPORTS IN OUR COUNTRY - Erkaboev Oybek Mukhammadjonovich (Proximus Journal Publishing, 2025)
This article analyzes the issues of forming an active and healthy lifestyle among women through the development of mass sports in the Republic of Uzbekistan. It scientifically illuminates the role of physical activity in strengthening women's health, social, psychological, and spiritual aspects of promoting a healthy lifestyle. The importance of the widespread promotion of mass sports in state policy and its role in increasing the social activity of women are also shown.
Keywords: mass sports; women's health; physical activity